Pengaruh Inflansi Dan Investasi Terhadap Pengangguran Di Provinsi Banten Tahun 2017-2021 - Muhayaroh Muhayaroh; Khusnul Khotimah; Tiara Rahmawati; Indina Indina; Pahmi Pahmi; Deris Desmawan (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Unemployment is a term for people who do not have a job. Unemployment occurs in many regions, including Banten Province. Unemployment is caused by an imbalance between work and the number of workers which increases every year. This creates intense competition between new jobs and old or experienced jobs. The purpose of this study was to determine the effect of inflation and investment on unemployment in Banten Province in 2017-2021. Researchers use secondary data for research. The analysis technique used in this study is multiple regression. High unemployment can increase tax bills, waste potential human resources, reduce opportunities for economic growth and cause personal and social losses such as confusion, anxiety, depression, crime and disruption of social order (Kurilis & Joseph, 2019). This suggests that high unemployment costs can reduce productivity and growth. Because it is important for the government to formulate policies to reduce the high unemployment rate. Unemployment affects inflation in a region so that it can affect economic growth in that area. Even though the level of social welfare is not a good indicator, it can be seen from an economic perspective that can be measured by national income per capita. To increase PN, economic growth is measured by GDP growth, which is one of the most important goals to be a chieved in economic development.